HomeWorks - Marcello Tavone (Footprint, 2018)
What if the city of the twenty-first century was not as we have imagined it? What if the culture of congestion was swept away by an isotropic, weak and diffused urban reality; by the culture of dispersion? A nebulous and potentially limitless city freed from any physical and symbolic centre, where uncertain attempts of urbanity overlap with the idealised landscape of the countryside.